The relationship between learning environment and learning motivation to natural and social sciences learning outcomes of the fourth-grade elementary school students - Azzahra, Zhyahira Mourischa Fatimah; Junaedi, Akhmad (Indonesian Journal of Science and Mathematics Education, 2024)
This study investigated the relationship between learning environment, learning motivation, and Natural and Social Sciences learning outcomes of the fourth-grade students of Gugus Mangkubumi, Klaten Regency. The method employed was quantitative, with an ex-post facto correlation research approach. The research population consisted of all fourth-grade students at Gugus Mangkubumi, with a sample size of 106 students selected using the saturated sampling technique. The analysis revealed a positive relationship between learning motivation and learning environment with Natural and Social Sciences learning outcomes. Learning motivation has a greater impact than the learning environment on learning outcomes. This study emphasizes the importance of focusing on students' intrinsic motivation and creating a conducive learning environment to help them achieve academic success. The study's findings highlight the importance of educational interventions that focus on developing intrinsic motivation and creating a supportive learning environment.